Arsenic deposition in different organs or tissues in an experimental toxicosis of White Newzealand Rabbit (Asian Journal of Medical and Biological Research, 2016)
The present study was undertaken for the detection of arsenic in different organs or tissues in an experimentally induced arsenicosis affected adult Newzealand white rabbits. The experiment was carried out on a total of 30 (01 month old) adult Newzealand white rabbits. Experimental arsenicosis were developed in rabbits by oral administration of arsenic trioxide alone and along with tannic acid, di-sodium hydrogen phosphate (DSHP), alum and As contaminated water after filtration using SCIF bed along with alum. For this, the rabbits were randomly divided in to six (6) equal groups (A,B,C,D,E & F) at the ratio of three males and two females in each group, rats of group A was kept as control without giving any treatment, rabbits of group B received arsenic trioxide@100ppm, group C received arsenic trioxide @ 100ppm plus tannic acid @100ppm, group D received arsenic trioxide @ 100ppm plus di-sodium hydrogen phosphate (DSHP) @100ppm, group E received arsenic trioxide @100ppm plus alum @100ppm orally daily for 60 days in all cases and group F received alum@100ppm in SCIF-bed filtrated water orally daily for 60 days. The different organs and tissues of both dead and sacrificed rabbits (Liver, kidney, heart, Lungs spleen, stomach, muscle and skin) were collected for detection of arsenic. Arsenic was detected qualitatively by Reinsch test, semiquantitatively by Merck Arsen test kit. The distribution of arsenic concentration was highest in liver and lowest in skin. It has been concluded that arsenic were deposited in different organs or tissues of rabbit in an experimentally induced arsenicosis as like as natural occurrence.Asian J. Med. Biol. Res. September 2016, 2(3): 422-428